Surgical treatment of implants affected by periimplantitis after 15 years of loading: A case report - Nícoli, Lélis Gustavo [UNESP]; Pigossi, Suzane Cristina [UNESP]; Marcantonio, Cláudio; Zandim-Barcelos, Daniela Leal [UNESP]; Marcantonio, Elcio [UNESP] (Wolters Kluwer, 2016)
Purpose: The aim of this case report is to describe the surgical treatment of 2 implants affected by periimplantitis after 15 years of loading. Materials and Methods: The treatment included mechanical and chemical decontamination with topical application of tetracycline associated with a regenerative approach. Both defects were filled with particulate autogenous bone from tuber and covered with resorbable collagen membrane. Results: The follow-up of 30 and 13 months of the implants 24 and 14, respectively, showed an absence of clinical signs of periimplant inflammation and near-complete bone regeneration. Conclusions: The therapy approach was effective in eliminating periimplant inflammation and promoting bone gain around the implants.
Keywords: Bone regeneration; Membrane; Tetracycline